Pengaruh Daur Ulang, Efisiensi Sumber Daya, dan Inovasi Produk terhadap Implementasi Ekonomi Sirkular - Aliatus Nurrochmah; Lola Via Marcellina; Tanya Tata Putri Srikandi; Felisya Natalia Purwanto; Maria Yovita R. Pandin (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of recycling, resource efficiency, and product innovation on the implementation of circular economy in the textile industry and plastic processing industry in East Java Province. Using a descriptive quantitative approach with secondary data from five companies over the period 2020-2024, this study found that recycling and resource efficiency have a positive and significant effect on the implementation of circular economy, while product innovation does not show a significant effect. The research model has a very high explanatory power (R² = 0.983), indicating that 98.3% of the variation in circular economy implementation can be explained by the three variables. The study also found a significant reciprocal relationship between circular economy implementation and recycling practices. This finding confirms the importance of optimizing recycling practices and resource efficiency in promoting a circular economy, while highlighting the need to align product innovation strategies to be more oriented towards the principles of sustainability and circularity in the context of industry in East Java.